Autoimmune Pancreatitis Type 1 Associated with a Pancreatic Pseudocyst - Hesse, Felix (Case Rep Gastroenterol, 2019)
Pancreatic cystic lesions comprise diverse entities with different histopathological characteristics. Differential diagnosis is often challenging. Autoimmune pancreatitis (AIP) is usually not considered an underlying pathology in the differential diagnosis of peri-/pancreatic pseudo-/cystic lesions. We report the case of a 73-year-old male with diffuse pancreatic enlargement and an adjacent cystic lesion (60 × 80 mm) on computed tomography scan. Based on these imaging findings and an elevated serum IgG4 concentration, AIP complicated by a pancreatic pseudocyst was diagnosed, and treatment with glucocorticoids was started. Regular follow-ups showed a good response to treatment with regression of the pancreatic pseudocyst and remittent pancreatic swelling.